Fit kids! : the complete shape-up program from birth through high school - Cooper, Kenneth H. (Nashville, Tenn. : Broadman & Holman, 1999)
An easy-to-follow fitness book for infants, children, adolescents, and teens that includes training instructions, meal plans, and reference charts to help children of every age make the best fitness and nutrition choices.
First ed. published by Bantam Books in 1991 under the title: Kid fitness.
Includes bibliographical references (p. 367-396) and indexes.
Adult
Keywords: Children -- Nutrition; Exercise for children; Physical fitness for children; Children -- Nutrition; Children -- Physical fitness; Exercise